Experimental Study on Slurry Improvement and Gushing Control in Water-rich Silty Fine Sand Layers - GUO Shiqing; CHEN Han; JIANG Peifeng; GUO Pengfei; SUN Yi; XU Pingbao; DI Honggui (Chengshi guidao jiaotong yanjiu)
[Objective] During EPB (earth pressure balance) shield tunneling through the water-rich silty fine sand layers, the ground is characterized by high friction, poor flow plasticity, and strong permeability. These features necessitate slurry improvement to enhance construction safety. [Method] Taking the section between Qinghe Road Station and Green Expo Park Station of Nanjing Metro Line 9 (hereinafter referred to as ′Line 9′) as case study, improvement agents including foam, bentonite, and clay are used to conduct slurry modification experiments. Thus, the optimal mass ratios between each agent and water are determined. On this basis, laboratory tests—including mixing, slump, and permeability tests—are conducted using both individual and combined improvement agents to define applicable range of slurry improvement in silty fine sand layers. A slurry improvement plan for water-rich silty fine sand is proposed, with a target slump of 125-175 mm and a permeability coefficient exceeding 1×10-3 cm/s as control indicators. [Result & Conclusion] In the optimization tests of individual improvement agents, the recommended BASF foam content is 3% by mass, the bentonite-to-water mass ratio should be 1∶9, and the clay-to-water ratio be 1∶5. Individual agents significantly improve the slump performance, and slurry modified with clay show better flow plasticity. Mixed agents exhibited lower mixing current and permeability coefficient compared to single agents, indicating their superior improvement in reducing slurry friction and permeability. Among the combinations tested, a foam-to-bentonite ratio of 2∶1 yielded better performance. The recommended slurry improvement schemes for water-rich silty fine sand layers are as follows: foam-only improvement plan with foam injection rate of 20%-30%; bentonite-only improvement plan with bentonite injection rate of 15%-20%; clay-only improvement plan with clay injection rate of 40%-45%; foam-bentonite 1∶1 agent improvement plan with agent injection rate of 20%; foaming-bentonite 2∶1 agent improvement plan with agent injection rate of 20%; and foaming-clay 1∶2 agent improvement plan with agent injection rate of 20%-40%.